2020
DOI: 10.3389/fphys.2020.533690
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Alleviates Skeletal Muscle Fibrosis via Attenuating Inflammation and Oxidative Stress

Abstract: The purpose of this study was to investigate the effect of exogenous hydrogen sulfide (H 2 S) treatment on skeletal muscle contusion. We established a skeletal muscle contusion model (S group) and an H 2 S treated of skeletal muscle contusion model (H 2 S group). Gastrocnemius muscles (GMs) were collected at day 1, day 5, day 10, and day 15 after injury, and comprehensive morphological and genetic analyses was conducted. H 2 S treatment reduced M1 macrophage (CD68), profibrotic cytokines (TGFβ), pro-inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 43 publications
1
17
0
1
Order By: Relevance
“…Previous studies have suggested that H 2 S alleviated the skeletal muscle fibrosis and partly improved skeletal muscle injury via oxidative stress inhibition [23]. Doxorubicininduced myocardial fibrosis was significantly attenuated by H 2 S via suppressing ROS production [24].…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have suggested that H 2 S alleviated the skeletal muscle fibrosis and partly improved skeletal muscle injury via oxidative stress inhibition [23]. Doxorubicininduced myocardial fibrosis was significantly attenuated by H 2 S via suppressing ROS production [24].…”
Section: Discussionmentioning
confidence: 96%
“…Our previous study has found that H 2 S alleviates renal injury and fibrosis in response to unilateral ureteral obstruction by attenuating macrophage infiltration ( Zhou et al, 2020 ). In addition, H 2 S donors are also found to alleviate bleomycin-induced lung fibrosis ( Du et al, 2019 ), transverse aortic constriction-induced myocardial fibrosis ( Liu et al, 2021 ) and blunt contusion-induced skeletal muscle fibrosis ( Zhao L et al, 2020 ) by attenuating oxidative stress. Consistent with these findings, the present study found that both GYY4137 and NaHS significantly decreased immobilization-induced leukocyte infiltration and oxidative stress, reduced the production of IL-1β and TGF-β in skeletal muscles, thus alleviating immobilization-induced muscle fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of NaHS at high dose of 10 mg/kg has been shown to induce lung inflammation by itself, and also to worsen CLP-induced lung inflammation ( Zhang et al, 2006 ). However, administration of NaHS at low dose of 0.5–2 mg/kg exerts anti-inflammatory effects in animal models of ovalbumin-induced airway inflammation ( Benetti et al, 2013 ), homocysteine-induced neuro-inflammatory conditions ( Kumar and Sandhir, 2019 ) and blunt contusion-induced skeletal muscle atrophy ( Zhao L et al, 2020 ). In consistent with these studies, our findings showed that both GYY4137 (50 mg/kg) and NaHS (20 μM/kg or 1.12 mg/kg) significantly inhibited immobilization-induced inflammation in skeletal muscles.…”
Section: Discussionmentioning
confidence: 99%
“…H 2 S donors have been widely used in vivo using animal models to treat various pathological conditions (Fagone et al, 2018). This includes reduction by the H 2 S donor NaHS of skeletal muscle atrophy in a mouse model of diabetes (Lu et al, 2020), or the decrease of muscle fibrosis after contusion-induced injury (Zhao et al, 2020). Interestingly, various therapeutics like Zofenopril have been shown to exert their effect through the indirect release of H 2 S (Fagone et al, 2018; Wallace et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…H 2 S has emerged as a promoter of the resolution of inflammation through the regulation of macrophage inflammatory state (Sun et al, 2020; Wallace et al, 2012). Interestingly, H 2 S-releasing molecules, like NaHS, have been shown to reduce skeletal muscle atrophy in a mouse model of diabetes (Lu et al, 2020) and to decrease muscle fibrosis after contusion-induced injury (Zhao et al, 2020). Moreover, H 2 S-releasing molecules have shown promising results in cardiovascular disorders and arthritis with reduced adverse effects (Wallace et al, 2020; Wallace et al, 2018).…”
Section: Introductionmentioning
confidence: 99%